KESESUAIAN UKURAN KONSTRUKSI UTAMA KAPAL PURSE SEINE DI PPN PEKALONGAN DENGAN ATURAN BIRO KLASIFIKASI INDONESIA - Muhammad Hafizh Adinugorho; Muhammad Imron; Fis Purwangka (Jurnal Perikanan Tangkap : Indonesian Journal of Capture Fisheries, 2018)
Fishing vessel is one of the units in fishery activities with high operational risk that can cause accidents, both ship and crew accidents. Most of the fishing vessels that operate in Indonesia were made traditionally without any planning. Fishing vessels in Pekalongan Fishing Port still built using traditional methods. Shipbuilding planning requires rules to produce ship construction that meets the standards. The rules that used as a reference is ship classification and ship construction from Biro Klasifikasi Indonesia (BKI). BKI was established by implementing technical standards in the activities of design and construction as well as maritime surveys related to floating facilities, including vessels and offshore construction. This study aims to obtain the cross-sectional dimension of some parts of the fishing vessel construction and to analyze the dimension appropriateness of Purse Seine in Pekalongan Fishing Port with BKI standard. This study was used purposive sampling and the data were collected using interview, observation, measurement, and literature study. The data were analyzed using numerically-comparative method. Some parts of fishing vessel constructions measured in this study consisted of keel; high bow; ivory; machine foundation; outer skin; and fences. Research showed that there are 53,18% of construction sizes that meets the criteria of BKI, while there are 46,83% of construction sizes does not meet the criteria of BKI.